Tribunal multiportas à luz do Código de Processo Civil - 2015 - Lobo, Mônica de Cassia Thomaz Perez (2021)
The national Judicial Powers of Western societies, without exception, have been going through difficult times and in search of better results to meet the demands of their societies. In Brazil the insertion of consensual means of conflict resolution started in Law with the edition of CNJ Resolution. 125/2010, and served as the basis for regulation by the Legislative, five years later, both under Law 13.140/2015 and CPC. Mediation and conciliation are consensual means existing in the Brazilian and foreign legal systems. They are forms of conflict resolution based on dialogue, consensus and hope for a faster and less burdensome solution for both contending parties. In this study we will make a historical return in order to show that consensual methods have their origins in practices that have long been inscribed in legal annals, not only, but also since the beginning of the organization of life in society. We will discuss jurisdiction and the evolution of self-composition means in several countries, both Civil Law and Common Law. In this context, starting from the demystification of the judicial process - which, in practice, dominates our legal culture, to modify it, encouraging the diffusion of methods to promote Justice - and the deconstruction of some dogmas that revolve around it, demonstrate that a change in society's thinking is absolutely necessary to, finally, deal with our conflicts in a peaceful, civic, friendly and human way. For this, it is essential to return individuals' autonomy to solve their own conflicts, empowering them. We will study its evolution in Brazil, the changes in paradigms and fostering them, including discussing the changes in relation to res judicata